BBC Learning English YouTube Channel as an Authentic Material to Improve Students’ Listening Skill - Herlisma, Intan; Rohayati, Dedeh; Faridah, Didih (Universitas Galuh, 2024)
This research aims to investigate 1) how the teacher implements the BBC Learning English YouTube Channel as authentic material to improve student listening skills; and 2) what the students’ perceptions of using BBC Learning English YouTube Channel as authentic material to improve students' listening skills. Case study was used as a research design in this study involving the participants of an English Teacher and six twelve-grade Vocational High School students. The data of this study were collected from observation and students’ interviews. The results of class observation showed that BBC Learning English YouTube Channel as authentic material is effective and helps the teacher in improving students’ listening skills. Meanwhile, the students' interview indicates the students’ positive perceptions on the implementation of the BBC Learning English YouTube Channel as authentic material. They argued that learning listening by using BBC Learning English YouTube Channel can motivate them to learn. The video shown assisted them to identify the topic of the material in the listening class and can improve their listening skill. Both results of observation and interviews showed that BBC Learning English YouTube Channel became an effective assistance for the teacher and students in teaching and learning listening skills.